ANALYSIS EFFECTIVITAS RELATING TO THE WAITING TIME IN CT SCANNING PROCEDURE BASED ON THE MALCOM BALDRIDGE APPROACH ON OUTPATIENT TREATMENT PATIENTS AT THE RADIOLOGY INSTALLATION OF THE CENTRAL POLICE HOSPITAL R. SAID SUKANTO - Leti Ratna Kusumawati; Munir Munir; Adang Bachtiar (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Introduction: Hospitals have the mission to provide excellent, comprehensive and standardized medical services in the context of improving people’s health conditional through among others reduced waiting time. Waiting time is the time used by a patient to receive health services beginning from at the registration counter to the doctor’s examination room. Method: This research used the Qualitative study. The research was conducted from April 2019 through May 2019 at the Outpatient Treatment Unit of the Radiology Installation of the Central Police Hospital R. Said Sukanto Jakarta The informants in this research were chosen based on the principle of suitability and sufficiency namely 8 informants; they were head of the Radiology Installation, a radiologist, a senior supervisor or radiographer, a registration counter officer, a nurse and 3 selected patients. The data collected in this study was primary data namely through in-depth interviews and direct observation, while secondary data was obtained through document reviewing. Analysis using Malcolm Baldrige framework Results: The result of this study indicates that the waiting time in CT Scanning procedures average 3 hours 1 minute and 25 seconds, which exceeds the standard stipulated by the Ministry of Health of the Republic of Indonesia the standard time ≤ 3 hours. Assessment aspect of Malcolm Baldrige the best is aspect organization profile, leadership and customer/ patient focus, an aspect have substantial effect on the waiting time in CT Scanning procedures. Mismatch between the theory and the result of this study may be caused by limitation in the research. Conclusion: In principle, services are already good except for few matters that need improvement namely on customer/patient care, strategic planning, measurement of analysis and management of knowledge as well as results in the organization. Keywords: Malcolm Baldrige criteria, CT Scanning procedure, waiting time